Feministische Anthropologie des Ersten Testaments. Beobachtungen, Fragen, Plädoyers (lectio difficilior, 2003)
The contribution to our „Forum“ poses some questions regarding a biblical feminist anthropology and brings theses into this discussion. The main question will be under which auspices female work with Hebrew keywords of anthropology (leb, næfæs etc.) can be sensible. After setting the question into the context of the history of theology, Silvia Schroer argues for a better inclusion of textexegetical work into critical feminist research of the history of civilisation. Without the wellfounded knowledge of cultures of the Ancient Near East, e.g. the Egyptian or Near Eastern concepts of the human being in certain times, without the knowledge of certain semantics of iconography, the work with Hebrew vocabulary is indeed irresponsible. However, through an interdisciplinary connection in the proposed way exciting results in regard to gender research can be expected.